Co-digestion of the hydromechanically separated organic fraction of municipal solid waste with sewage sludge. (1st January 2015) - Borowski, Sebastian
Abstract: This study investigates the anaerobic digestion of the hydromechanically sorted organic fraction of municipal solid wastes (HS-OFMSW) co-digested with sewage sludge (SS). Eight laboratory-scale experiments were conducted under semi-continuous conditions at 15 and 20 days of solids retention time (SRT). The biogas yield from the waste reached 309 to 315 dm 3 /kgVS and 320 to 361 dm 3 /kgVS under mesophilic and thermophilic conditions, respectively. The addition of SS to HS-OFMSW (1:1 by weight) improved the C/N balance of the mixture, and the production of biogas through anaerobic mesophilic digestion increased to 494 dm 3 /kgVS, which corresponded to 316 dm 3 CH4 /kgVS. However, when SS and HS-OFMSW were treated under thermophilic conditions, methanogenesis was inhibited by volatile fatty acids and free ammonia, which concentrations reached 5744 gCH3 COOH/m 3 and 1009 gNH3 /m 3, respectively. Highlights: Water separated municipal organic waste was co-digested with sewage sludge. The maximal biogas production from the mixture was achieved at 35 °C. Thermophilic co-digestion process was inhibited by volatile fatty acids. The highest free ammonia concentrations were detected in thermophilic co-digestion.